If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7 + -1a) = 14 (7 * 2 + -1a * 2) = 14 (14 + -2a) = 14 Add '-14' to each side of the equation. 14 + -14 + -2a = 14 + -14 Combine like terms: 14 + -14 = 0 0 + -2a = 14 + -14 -2a = 14 + -14 Combine like terms: 14 + -14 = 0 -2a = 0 Solving -2a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '-2'. a = 0 Simplifying a = 0
| x/2=-17 | | (.5x-73)=90 | | 5(6x+7)=28-(5x+7) | | 22+x=22-x | | -3(w-5)=-7w+31 | | -4+7(-7-5n)= | | -4u-3=9(u+4) | | -8(4+n)-8= | | 11x=222 | | 0.22y+0.03(y+4000)=2370 | | 3c+9c= | | q-9=-19 | | 4v-15=49 | | -9(v-4)=5v+4 | | .4x-73=90 | | -8(4+n)= | | 9-9=-19 | | 5+-(11)-(-11)= | | 15u+5v-3u+17v= | | -19+p=-9 | | 7(2x-10)-3=7(x-5)+4 | | -19+p=9 | | 8=16.9-a | | cosine(x)=-0.25 | | 8x-4(1+X)= | | 10=.11(0)+b | | X*x+1=101 | | 6/5÷6/ | | 2x+3+x=128 | | F(x)=log(x+7)+4 | | 6/5÷6/8 | | 7x-6+10x-5= |